2006
DOI: 10.1292/jvms.68.515
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Antimicrobial-Resistant Campylobacter jejuni on Japanese Broiler Farms

Abstract: ABSTRACT. We investigated for dynamics of Campylobacter clones on 2 different managerial broiler farms. Campylobacter isolates were differentiated by resistance typing and molecular typing methods. On farm I, the same C. jejuni clones resistant to fluoroquinolone and oxytetracycline were isolated after one and half years again and another susceptible clone was invaded. The susceptible clone was isolated again after half year. Broiler flocks on the farm may be repeatedly infected with a few C. jejuni clones. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…clones to continue to persist on broiler farms as a consequence of infection carry-over between chicken flocks. This hypothesis is supported by a previous study, in which specific C. jejuni clones were detected in chicken flocks at different time periods on broiler farms [10]. It is also possible that colonized broiler flocks contaminate the environment around broiler farms.…”
supporting
confidence: 79%
“…clones to continue to persist on broiler farms as a consequence of infection carry-over between chicken flocks. This hypothesis is supported by a previous study, in which specific C. jejuni clones were detected in chicken flocks at different time periods on broiler farms [10]. It is also possible that colonized broiler flocks contaminate the environment around broiler farms.…”
supporting
confidence: 79%
“…The administration of fluoroquinolone to livestock has been regarded as a major cause of the increase in resistant strains Gupta et al, 2004 . However, more recent studies have reported the detection of resistant strains at farms where fluoroquinolones have not been used Asai et al, 2007;Ishihara et al, 2006 . This finding indicates that the occurrence of resistant strains is not necessarily linked to the use of antibacterial agents at farms.…”
Section: Discussionmentioning
confidence: 99%
“…National level monitoring helps to realize broad prevalence of antimicrobial resistance: however, it is unable to fully figure out variability of antimicrobial resistance prevalence among farms or among herds and individuals on a farm. Detection of antimicrobial-resistant bacteria on farms usually means that the bacteria have developed antimicrobial resistance by genetic mutations or acquisition of resistance genes [41], and other resistant clones have intruded into the farms [73]. In either case, the use of antimicrobials frequently acts as selective force.…”
Section: Future Issuementioning
confidence: 99%